Permanent magnet synchronous and brushless DC motor drives. - Krishnan, R., ....- (Boca Raton : CRC, 2010)
Unlike most books on machine drives, Permanent Magnet Synchronous and Brushless DC Motor Drives provides comprehensive treatment of standard and low cost converter topologies and integrated control of the motor drive system. After an introduction to machines, power devices, inverters, and control, this book presents detailed coverage of PM synchronous machines, including modeling, implementation, control strategies, flux weakening operations, parameter sensitivity, and rotor position sensorless control. Subsequent chapters address the simulation, control, inverters topologies, and commutation torque ripple of pm brushless dc motor drives. MATLAB® codes are also included throughout the text where appropriate.